3(2x-1)+12=x

Simple and best practice solution for 3(2x-1)+12=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-1)+12=x equation:


Simplifying
3(2x + -1) + 12 = x

Reorder the terms:
3(-1 + 2x) + 12 = x
(-1 * 3 + 2x * 3) + 12 = x
(-3 + 6x) + 12 = x

Reorder the terms:
-3 + 12 + 6x = x

Combine like terms: -3 + 12 = 9
9 + 6x = x

Solving
9 + 6x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
9 + 6x + -1x = x + -1x

Combine like terms: 6x + -1x = 5x
9 + 5x = x + -1x

Combine like terms: x + -1x = 0
9 + 5x = 0

Add '-9' to each side of the equation.
9 + -9 + 5x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 5x = 0 + -9
5x = 0 + -9

Combine like terms: 0 + -9 = -9
5x = -9

Divide each side by '5'.
x = -1.8

Simplifying
x = -1.8

See similar equations:

| 9+2-4=x-2 | | 2x+13+2x-18=180 | | 9x+230=5 | | x/2=-8+x | | x+7+2=4-1 | | 2x-18=2x+13 | | 2x+13=2x-18 | | y=3px+6p^2y^2 | | 3x+7+7x+2+79=90 | | -7+x=13-1 | | 4x+15=7x-20 | | -111=7n+2(6n-8) | | 2(5k+3)-14k+6+3= | | x+7-3x-5=2 | | (2x+3)(4x-2)=-6 | | -11=7n+2(6n-8) | | 3x+7=7x+2 | | x/4=2x-1/3 | | 135=5(4m+6)-5m | | -7(x-4)-5x=112 | | 3-4x=x-12 | | 8x-6(3-6x)=-370 | | b=100+-1m+-1s | | 3+8=7 | | b+s+m=100 | | 15x+3x-12=78 | | -3.250+-3.333= | | 3x-y=5(y+2x) | | 2x+7=46x | | (-2)-(1.875)= | | x^2+10x+25=1000 | | -2-1.875= |

Equations solver categories